2007
DOI: 10.1055/s-2006-958701
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Monoclonal Antibody to Intercellular Adhesion Molecule-1 in Venous Ischemia-Reperfusion Injury: Experimental Study in Rats

Abstract: Flaps with venous occlusion have a decreased survival rate compared with arterial occlusion. It seems that several factors are involved in the etiology of total venous occlusion, including free radicals, edema, thrombosis, and reperfusion injury. In the present study, the authors evaluated the blockage of polymorphonuclear leukocyte endothelial adhesion by using a monoclonal antibody to the intercellular adhesion molecule 1 (ICAM-1) ligand to prevent venous ischemia-reperfusion injury in rat epigastric island … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Bilgin‐Karabulut et al also demonstrated that the antioxidants vitamins E and A decrease tissue injury in the venous ischemia‐reperfusion model in the skin flap of the rat . In addition, Demiseren et al have shown that the intercellular adhesion molecule‐1 antibody prevents adhesion of the inflammatory neutrophils by interfering with the endothelium and can reduce venous ischemic tissue injury …”
Section: Discussionmentioning
confidence: 99%
“…Bilgin‐Karabulut et al also demonstrated that the antioxidants vitamins E and A decrease tissue injury in the venous ischemia‐reperfusion model in the skin flap of the rat . In addition, Demiseren et al have shown that the intercellular adhesion molecule‐1 antibody prevents adhesion of the inflammatory neutrophils by interfering with the endothelium and can reduce venous ischemic tissue injury …”
Section: Discussionmentioning
confidence: 99%
“…In addition, HUVEC are isolated from large veins, while the endothelial inflammatory response associated with ischemia/reperfusion injury is most pronounced in the venular microvasculature (10). (4,(45)(46)(47) or adhesion molecule deficient animals (48,49). Inhibition of selectin function has reduced inflammation and fibrosis in a large animal model of warm and cold ischemia (46 (50,51), however, multicenter randomized trials did not confirm this effect (52); success being limited perhaps by the redundancy of adhesion molecule/leukocyte interactions in vivo (53,54 …”
Section: Leukocyte Recruitment To Hypoxia-stimulated Endothelial Cellmentioning
confidence: 99%
“…One approach has been the use of T-cell depleting therapies, such as antilymphocyte globulin (41)(42)(43)(44), which, by affecting T-cell number and function, works late in the inflammation/immune activation cascade. Leukocyte recruitment has previously been inhibited in animal models of ischemia/reperfusion and transplantation using antiadhesion molecule therapy (4,(45)(46)(47) or adhesion molecule deficient animals (48,49). Inhibition of selectin function has reduced inflammation and fibrosis in a large animal model of warm and cold ischemia (46).…”
Section: Clinical Relevance To Transplantationmentioning
confidence: 99%
“…Rats were followed for 7 days after which the flaps were histologically assessed. In the case of eight hours of ischemia, ICAM-1 antibody treatment had a clear beneficial effect significantly increasing the viable area [45]. Different approaches, e.g.…”
Section: The Integrin Ligand Icam-1 As a Therapeutic Targetmentioning
confidence: 99%